Impact analysis of residential induction cooking on medium voltage distribution network system: A case study of Nagarkot feeder, Bhaktapur, Nepal - Bhattarai, Sanjip; Maharjan , Sanjeev (Journal of Innovations in Engineering Education, 2021)
Electricity is mostly used for cooking purposes in developed countries for a long time. Electricity could be used for cooking in Nepalese residential areas by transfering from Liquifty Petroleum Gas (LPG) to Induction Cooking(IC). Signiﬁcant use of IC to the distribution feeder can increase the losses of the feeder, reducing the voltage proﬁle at the buses, which in fact increases the current-carrying conductor. So, the grid impact analysis by IC loading to the distribution feeder is necessary. The study is carried out by performing technical analysis by load ﬂow analysis on the feeder by calculating current, voltage proﬁle, and power losses. The load ﬂow has been performed for diﬀerent loading of IC, and optimized Distributed Generation (DG) size is calculated. The bundling of the conductor is performed to reduce the loss at the feeder. This can be performed by checking the rated current of the conductor used (i.e., the branches where the rated current limit violates then that branches need bundling). The power loss at a diﬀerent penetration level of IC is calculated. The IC power rating of 1500 Watts at each residential consumer when total 4924 number of the consumer is loading to Nagarkot feeder, active power loss increases to 1887.013 kW from 469.443 kW, and reactive power loss increases to 943.507 kVar from 234.722 kVar. The Minimum voltage is 0.664 Per unit (pu) at bus number 104 (Halede bus) which violates the voltage stability limit. The optimal penetration level of IC can be done up to 25% of total peak load by DG integration of 5965 kVA at 0.8 Power Factor (pf) lagging. This will give an active power loss of 530 kW. The next method, i.e., bundling of the conductor in 9 number of branches (at branch number 1, 2, 31, 34, 36, 38, 78, 79, and 86), should be done to improve the IC loading level. The maximum IC loading can be done up to 40% of the total peak load with a power loss of 477.7 kW by this bundling technique.